Understanding impacts and barriers to adoption of climate-smart agriculture (CSA) practices in North-Western Nigerian drylands. Issue 1 (1st January 2021) - Jellason, Nugun P.; Conway, John S.; Baines, Richard N.
ABSTRACT: Purpose: Empirical evidence suggests that climate-smart agriculture (CSA) practices will promote resilience against climate change. We explored location-specific CSA practices and strategies for adoption in two communities (Zango and Kofa) in the North-Western Nigerian drylands. Design/methodology/approach: Mixed methods design was employed with thirty smallholders per community selected from a baseline study of 220 smallholders from the two study communities. Smallholders were engaged in a farmer participatory learning and action (PLA) on CSA adoption for resilience. Impacts of PLA were evaluated six months post-implementation and barriers for adoption explored. Findings: Pre- and post-PLA training indicated a change in confidence to adopt some CSA practices. Both communities showed greater confidence ( p < .05) related to solving climate-related problems and the use of fertiliser. Communities differed in relation to other factors: Kofa exhibited improved confidence (71.4%) in solving water challenges while Zango showed greater confidence (76%) in relation to solving environmental problems. We found gender-responsive CSA promote women participation in farming. Practical implications: A deep understanding of the underlying reasoning behind non-adoption of CSA practices could support future climate resilience policies, and the lead-farmer extension model could reduce extension agent-farmer ratio. Theoretical implications: Identification of climate-smart agriculture practices and their adoption confirms the benefit of participatory learning for transformation, in this case, empowerment of smallholders, including women, to adapt to climate change in a wider sub-Saharan Africa context. Originality/value: This study explores PLA application in supporting the uptake of CSA practices for resilience and advancement of lead-farmer extension for reducing extension agent-farmer ratio. GRAPHICAL ABSTRACT: